Security politics in Japan legislation for a new security environment - Hosoya, Yu?ichi 1971- (Japan library (Shuppan Bunka Sangyo? Shinko? Zaidan))
How can peace be realized in the modern world? And how can Japan ensure its own security? Despite the intense debates over Japan's recent security-related legislation, such vital issues as these were never explored. To give proper consideration to these thorny questions, it is indispensable to have both a knowledge of history indicating the circumstances in which wars occur and a real recognition of the security environment of the 21st century. This work explores hotly debated security-related matters from a standard viewpoint on international politics and diplomatic history. It also advocates in a bold yet level-headed manner the form Japan's security should take and the path Japan should follow to make that a reality."